Research progress on albumin-based hydrogels: Properties, preparation methods, types and its application for antitumor-drug delivery and tissue engineering - Meng, Run; Zhu, Huimin; Deng, Peiying; Li, Minghui; Ji, Qingzhi; He, Hao; Jin, Liang; Wang, Bochu (Frontiers in Bioengineering and Biotechnology, 2023)
Albumin is derived from blood plasma and is the most abundant protein in blood plasma, which has good mechanical properties, biocompatibility and degradability, so albumin is an ideal biomaterial for biomedical applications, and drug-carriers based on albumin can better reduce the cytotoxicity of drug. Currently, there are numerous reviews summarizing the re-search progress on drug-loaded albumin molecules or nanoparticles. In comparison, the study of albumin-based hydrogels is a relatively small area of research, and few articles have systemati-cally summarized the research progress of albumin-based hydrogels, especially for drug deliv-ery and tissue engineering. Thus, this review summarizes the functional features and prepara-tion methods of albumin-based hydrogels, different types of albumin-based hydrogels and their applications in antitumor drugs, tissue regeneration engineering, etc. Also, potential directions for future research on albumin-based hydrogels are discussed.